GHERS: Greater Harvest and Economic Returns from Shrimp: Final program performance report - WorldFish (WorldFish, 2013)
The Greater Harvest and Economic Returns from Shrimp (GHERS) is an initiative of Poverty Reduction by Increasing the Competitiveness of Enterprises (PRICE) project, funded by USAID. The objective of GHERS was to increase the productive capacity of existing farms and enhance quality of shrimp delivered to processors adding over $ 45 million to current sales, $10 million new investment and 14,000 new jobs. This final performance report presents the activities and achievements of the project since 2008.